Quantum mechanical three-dimensional wavepacket study of the O(1D)+ClH?ClO+H reaction - Gogtas, F; Bulut, N; Akpinar, S (Elsevier Science Bv, 2003)
The state-to-state reaction probabilities at zero total angular momentum have been calculated for the O(D-1) + ClH --> ClO + H reaction. Reaction probabilities from the ground state of ClH and going to all possible open product channels are computed over a wide range of energies. The energy dependence of the reaction probabilities shows that the reaction is strongly dominated by resonances. The product rotational and vibrational distributions are also extracted. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: wavepacket; resonances; state-to-state reaction probabilities